2016
DOI: 10.1530/erc-16-0287
|View full text |Cite
|
Sign up to set email alerts
|

Whole blood mRNA in prostate cancer reveals a four-gene androgen regulated panel

Abstract: Due to increased sensitivity, the expression of circulating nucleotides is rapidly gaining popularity in cancer diagnosis. Whole blood mRNA has been used in studies on a number of cancers, most notably two separate studies that used whole blood mRNA to define non-overlapping signatures of prostate cancer that has become castration independent. Prostate cancer is known to rely on androgens for initial growth, and there is increasing evidence on the importance of the androgen axis in advanced disease. Using whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Because the ovary is also responsible for the synthesis of AR, it would be of great importance the search for biomarkers related to this protein 2830 . Interestingly, our results from KPM demonstrated that BORIS is partly responsible for the regulation of AR gene expression, and in turn, AR establishes a gene regulatory network with genes such as FN1 , CD97 , and FAM129A , which are related with poor prognosis, chemoresistance, and metastasis in several cancers, including OC 3133 . Previous studies are limited to the identification of possible target genes by evaluating changes in gene expression by increasing or decreasing BORIS levels; 5,6,11,19,34 however, our de novo pathway enrichment analysis allowed us to perform a novel selection (based on hundreds of experimental data available in public databases) of potential genes relevant in cancer, which are closely related through AR and BORIS.…”
Section: Discussionmentioning
confidence: 80%
“…Because the ovary is also responsible for the synthesis of AR, it would be of great importance the search for biomarkers related to this protein 2830 . Interestingly, our results from KPM demonstrated that BORIS is partly responsible for the regulation of AR gene expression, and in turn, AR establishes a gene regulatory network with genes such as FN1 , CD97 , and FAM129A , which are related with poor prognosis, chemoresistance, and metastasis in several cancers, including OC 3133 . Previous studies are limited to the identification of possible target genes by evaluating changes in gene expression by increasing or decreasing BORIS levels; 5,6,11,19,34 however, our de novo pathway enrichment analysis allowed us to perform a novel selection (based on hundreds of experimental data available in public databases) of potential genes relevant in cancer, which are closely related through AR and BORIS.…”
Section: Discussionmentioning
confidence: 80%
“…Several groups have showed that FAM129A is overexpressed in several cancer subtypes (Matsumoto et al 2006, Ito et al 2009, Thomas et al 2016. Additionally, the human protein atlas analysis, which evaluated tissue array based on immunohistochemistry for numerous proteins in normal tissues and over 200 tumor subtypes from 20 different cancer and cell lines, demonstrated that FAM129A is overexpressed in colorectal cancer, breast…”
Section: Discussionmentioning
confidence: 99%
“…Among these markers, FAM129A (aliases C1orf24, NIBAN and GIG39) has been reported to be overexpressed in various human cancer, strengthening its pathogenic relevance (Majima et al 2000, Adachi et al 2004, Matsumoto et al 2006, Ito et al 2009, Thomas et al 2016. FAM129A (family with sequence similarity 129 member A) gene is mapped on chromosome 1q25.3 and codifies a protein predominantly expressed in the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, FLNA has already been proposed in a clinical validated PCa biomarker panel in serum [74]. PSMA7 was also proposed as a PCa biomarker [55], and KRT7 is included in a whole blood mRNA 4-gene androgen regulated panel for PCa diagnosis [33]. Considering the relative expression levels of our HMGB1 and HMGB2 interactome targets in noncancerous cells or in blood of health subjects differ quite notably (Figure 7), one might anticipate that more sensitive analyses could be carried out using as biomarkers those proteins that are usually lowly expressed in noncancerous cells; thus, their levels are also low in the blood of healthy individuals.…”
Section: Discussionmentioning
confidence: 99%